Pd-Catalyzed Synthesis of Allylic Silanes from Allylic Ethers - Moser, Ralph (2010)
[Image: see text] Allylic phenyl ethers serve as electrophiles towards Pd(0) en route to a variety of allylic silanes. The reactions can be run at room temperature in water as the only medium using micellar catalysis.